Genetically Modified Mosquito: Myth and Reality - Yean, Teh Su; Lye, Koh Hock; Lee, Yeap Kiew (Journal of Science and Technology, 2012)
Sterile Insect Technique (SIT) has been applied successfully in some agricultural pest control programs in the past, but in many cases, success has not been sustainable in the long run. Various attempts have been made to duplicate this limited success SIT application in agriculture to other areas of applications, particularly in vector control. For example, a recent mosquito control program has been initiated in Malaysia to eliminate dengue-mosquitoes Aedes aegypti by releasing large amount of genetically modified GM male mosquitoes into the field to outcompete the wild male mosquitoes. Field experimental data that has been made available in the literature is limited, rendering it difficult to make independent assessment on its short-term efficacy and long-term sustainability of this GM control strategy. This paper presents a preliminary assessment of the effectiveness of GM mosquito in controlling dengue mosquito population by means of model simulations via DEER (Dengue Encephalitis Eradication Routines). Preliminary results indicate negative conclusion regarding the effectiveness of GM mosquitoes in controlling wild A. aegypti population over the long-term. Essentially, significant reduction of wild mosquito population is possible only if large over-flooding ratios are applied. Further, repeated releases must be maintained over an infinite time horizon to continue to sustain low population of mosquitoes. Major difficulty remains to be resolved. In particular, in-depth costbenefit analysis on this control program is essential to ensure long-term institutional and social support.